SUM SIGNED GRAPHS – II - Athira P. Ranjith; Joseph Varghese Kureethara (Ural Mathematical Journal, 2023)
In this paper, the study of sum signed graphs is continued. The balancing and switching nature of the graphs are analyzed. The concept of  \(rna\) number is revisited and an important relation between the number and its complement is established.